2012
DOI: 10.1186/1748-717x-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Dose-escalation using intensity-modulated radiotherapy for prostate cancer - evaluation of quality of life with and without 18F-choline PET-CT detected simultaneous integrated boost

Abstract: BackgroundIn comparison to the conventional whole-prostate dose escalation, an integrated boost to the macroscopic malignant lesion might potentially improve tumor control rates without increasing toxicity. Quality of life after radiotherapy (RT) with vs. without 18F-choline PET-CT detected simultaneous integrated boost (SIB) was prospectively evaluated in this study.MethodsWhole body image acquisition in supine patient position followed 1 h after injection of 178-355MBq 18F-choline. SIB was defined by a tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…20 Few studies have reported on the outcome after delivering SIB-IMRT. [20][21][22] Fonteyne et al detected an IPL in 118 of 221 PC patients using MRI and MRS. Median dose delivered to the prostate and the IPL was 78 Gy and 81 Gy respectively in 38 fractions.…”
Section: Simultaneous Integrated Boost In the Primary Setting For Pcmentioning
confidence: 99%
“…20 Few studies have reported on the outcome after delivering SIB-IMRT. [20][21][22] Fonteyne et al detected an IPL in 118 of 221 PC patients using MRI and MRS. Median dose delivered to the prostate and the IPL was 78 Gy and 81 Gy respectively in 38 fractions.…”
Section: Simultaneous Integrated Boost In the Primary Setting For Pcmentioning
confidence: 99%
“…Pinkawa et al 32 have demonstrated the feasibility of using 18 F-choline-PET/CT to allow dose escalation using a simultaneous integrated boost during radical radiotherapy, although the long-term survival data from such an approach is unknown. Vees et al 33 combined 99m Tc-Nanocoll prostatic sentinel lymph node detection using SPECT/CT with 18 F-choline-PET/CT in 20 men with high-risk prostate cancer; 40 per cent of patients had nodal involvement outside the standard pelvic radiotherapy target volume, highlighting that this approach may allow for tailoring of the radiotherapy treatment volume.…”
Section: Radiotherapy Planningmentioning
confidence: 99%
“…Studies have been performed on the brain using 18 F-FDG (65) and O-(2-18 F-fluoroethyl)-L-tyrosine PET (66), on head-and-neck tumors using 18 F-FDG PET (67-69), on prostate tumors using 18 F-fluorocholine PET (70), and on lung tumors using 18 F-FDG PET (71). Further clinical studies are ongoing.…”
Section: Tumor Boostingmentioning
confidence: 99%